Dead man's wake eaudiobook - Doiron, Paul (Mike Bowditch Mystery, 2023)
"Henry Leyva's narration shapes the story wonderfully because he keeps his regional accents in line with the writer's intent." — Audiofile on Hatchet Island Game Warden Mike Bowditch's engagement party is interrupted by the discovery of a gruesome double murder in this new thriller from Edgar Award-winning author Paul Doiron. On the evening of their engagement party, Maine Game Warden Investigator Mike Bowditch and Stacey Stevens witness what seems to be a hit-and-run speedboat crash on a darkened lake. When they arrive at the scene, their spotlight reveals a gruesome sight: a severed arm floating just beneath the surface. As day breaks, the warden dive team recovers not one but two naked corpses: a dismembered man and the married woman with whom he was having an affair. Mike begins to suspect the swimmers' deaths were not a senseless accident but a coldly calculated murder. Meanwhile, the hunt is on for the mysterious boater. Suspects abound on the lake, nicknamed "Golden Pond," including the violent biker husband of the murdered woman who may have taken vengeance on his wife and her paramour; a strange woman who claims to have witnessed the crash, but then changes her story; a very aggressive realtor and his wife who were determined to catch trespassers; and the lake's earnest young constable whose eagerness to help may hide darker motives. Alone among his fellow officers, Mike starts to sense the involvement of a trained marksman, smarter and more dangerous than any enemy he has ever faced before. As Mike and Stacey get closer to identifying the killer, their own lives are suddenly on the line as they confront a lethal killer who plans to silence them forever. The finale is a tour de force of drama and suspense. A Macmillan Audio production from Minotaur Books.